Pentas - Fathu Razzieq bin Osman (Trends in Undergraduate Research, 2023)
The site is located among 3 important areas that are Dewan Suarah, SJK Chung Hua Bau and residential areas. To make sure that the site will be used by anyone from these 3 areas, a concert venue was proposed inside the site. This concert venue will attract people either from Bau or visitors from outside the Bau area. This temporary structure is unique because of its materials that are made of scaffolding, timber and mesh fabric. The performance stage will be in the middle of the site to give people a whole-site view of a programme. The stage is surrounded by a gazebo and multipurpose area. The multipurpose area will have a landscape, rooftop platform, hammock and seating area. The gazebo can be used as seating space or as small vendor stalls, for sale of beverages. When there is no need for the structure, it can be dismantled and kept for future re-use.